Elaboración y aplicación de una guía para fortalecer el rendimiento académico ante los problemas intrafamiliares que tienen los estudiantes del 9º y 10º años de educación básica del colegio Victoria Vasconez Cuvi, sección nocturna, parroquia la matriz cantón Latacunga, provincia de Cotopaxi durante el año lectivo 2012 - 2013 - Bustos Sánchez, Natali Elizabeth (2013)
The human being reached its development and integral formation in base of the education that it has received so while more educated a town is; more advanced it will be in its progress and evolution. However, there are several difficulties oround this particular situation. One of the most important issue in the educational context is the domestic problems. It is a factor that determines the academic performance in teenegers. It is important to recognize that the family is a set of people who live underneath the same roof. Therefore each member must fulfill different roles with responsability. So, parents as a head of the household should educate their children with values based on, respect, discipline, good relationships and honesty. The family evironment is neither the result of the causality nor of the luck. It is the result of contributions of the whole members of the family. The academic assignments must be the developed in an effective, confident and self-esteem environment, which allow the students value themselves and stimulate the performance of their obligations and responsabilities assigned.